FORMULASI SERUM MINYAK ATSIRI TIMI DAN CENGKEH SERTA UJI AKTIVITAS ANTIOKSIDAN DENGAN METODE DPPH - Liem, Marcella; Monica, Eva; Yanuar, Michael Resta (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Essential oils from thyme (Thymus vulgaris) and clove (Syzygium aromaticum) are natural antioxidants with significant potential to neutralize free radicals. This study aims to evaluate the antioxidant properties of a serum containing a blend of these essential oils using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. It also aims to determine which serum formulation meets the required physical quality standards. The assessment includes organoleptic analysis, pH measurement, viscosity, homogeneity, spreadability, adhesiveness, globule size distribution, stability, emulsion type, hedonic evaluation, and antioxidant activity. The results indicate that the serum is in liquid form, with a pH between 5.149±0.227 and 5.447±0.109, viscosity ranging from 817.1±3.8 to 2083±0.00 cPs, adhesiveness lasting 5.45±0.26 to 11.210±0.09 minutes, and spreadability between 2.32±0.016 and 2.71±0.053 cm. Hedonic testing revealed that F1 was the most preferred formulation. Antioxidant activity analysis showed moderate to very weak effects, with IC50 values of 145.628 ppm (F1), 413.658 ppm (F2), and 536.529 ppm (F3). F1, which contains 4.5% clove essential oil and 1.5% thyme essential oil, demonstrated the best balance of physical properties and antioxidant activity among the tested formulations.